Control Method for Electromagnetic Unmanned Robot Applied to Automotive Test Based on Improved Smith Predictor Compensator. (28th July 2015) - Chen, Gang; Zhang, Weigong
A new control method for an electromagnetic unmanned robot applied to automotive testing (URAT) and based on improved Smith predictor compensator, and considering a time delay, is proposed. The mechanical system structure and the control system structure are presented. The electromagnetic URAT adopts pulse width modulation (PWM) control, while the displacement and the current doubles as a closed-loop control strategy. The coordinated control method of multiple manipulators for the electromagnetic URAT, e.g., a skilled human driver with intelligent decision-making ability is provided, and the improved Smith predictor compensator controller for the electromagnetic URAT considering a time delay is designed. Experiments are conducted using a Ford FOCUS automobile. Comparisons between the PID control method and the proposed method are conducted. Experimental results show that the proposed method can achieve the accurate tracking of the target vehicle's speed and reduce the mileage derivation of autonomous driving, which meets the requirements of national test standards.